Lime and NPK Effect on Soil Acidity and Yield of Barley in Different Acid Soils of Southern Region, Ethiopia - Boke, Shiferaw; Fekadu, Anteneh (International Journal of Natural Sciences Research, 2014)
In southern region acid soils cover appreciable areas of arable land and reduce or cause total failure of some sensitive crop yield. Barley is the most sensitive crop to soil acidity. A field experiment was carried out for three years (2007 to 2009) on loam Haplic Alisols of Chencha and clay loam Dystric luvisols of Hagerselam, Southern Region of Ethiopia, to evaluate the response of food barley and change in soil acidity to applied lime and NPK fertilizers. The study comprises three levels of calcitic lime (no lime, half and full doses of the recommend lime rate) and five different combinations of N-P-K fertilizers at the rate of 46-40-50 kg ha-1 (no fertilizer, NP, NK, PK, and NPK). The experimental design was factorial randomized complete block with three replications. Results obtained showed that application of lime and all combinations of fertilizers, either alone or combined, significantly (p < 0.05) increased barley yield over untreated control. The highest barley grain yield (2792 and 3279.3 kg ha-1) was recorded from combined application of NPK and half the recommended lime rate (3.84 and 0.85 t/ha at Chencha and Hagerselam, respectively) in 2007 when lime is freshly applied. In 2008 and 2009, when lime is used as residual effect, highest barley grain and biomass yields were obtained from applications of full lime rate + NPK. NPK application either alone or with lime gave better barley yield, which might suggest the importance of balanced (NPK) fertilizer application. The efficiency of fertilizers increased in the order of NP<NK<PK<NPK for Alisols of Chencha and NK<PK<NP<NPK for Luvisols of Hagereselam, with the effects accentuated more in the limed than in the un limed treatments. Liming 1.75 to 7.68 Mg ha-1 decreased the concentration of surface (0-30 cm) soil exchangeable aluminum by 50 to 80 per cent and increased pHw by 0.5 to 1.3 units after one month of application. Half and full recommended lime rates had statistically similar direct and residual effect on barley yield in both investigated soils; hence, applying half the recommended lime rate can be used without significant yield loss.